Technology Based Educational Learning Strategies to Develop Critical Thinking Skill in Islamic Religious Education in the Digital Era - Atikah, Za'imatul; Maftuhah; Abdelghani El Mousaoui (AT-TAJDID: Journal of Islamic Education, 2026)
The digital era presents new challenges and opportunities in education, particularly in developing students' critical thinking skills, especially in Islamic education. This study aims to discuss effective educational strategies based on technology to enhance critical thinking abilities within the context of Islamic Education. The research approach used is a literature review that analyzes various relevant theories and best practices. The findings indicate that the integration of technology in learning, such as the use of interactive discussion-based apps, online learning platforms, and computer-based simulations, can improve students' analytical, evaluative, and problem-solving abilities in the context of Islamic education. This strategy also involves designing collaborative, contextual, and problem-solving-oriented learning activities. The conclusion is that the wise use of technology in learning not only improves the quality of education but also prepares students to face complex challenges in the digital era.